TAB2 Promotes the Stemness and Biological Functions of Cervical Squamous Cell Carcinoma Cells - Yijia Zhou; Yuandong Liao; Chunyu Zhang; Junxiu Liu; Wei Wang; Jiaming Huang; Qiqiao Du; Tianyu Liu; Qiaojian Zou; Hua Huang; Pan Liu; Shiyin Ooi; et al. (Stem Cells International)
Cancer stem cells are a key population participating in the promotion of the cervical cancer progression through interacting with cancer cells. Existing studies have preliminary revealed that cervical cancer stem cells contribute to tumor recurrence and chemotherapy resistance. However, the specific mechanisms involved in regulating cell functions remain largely unknown. Here, we analyzed published data from public databases and our global transcriptome data, thus identifying cancer-related signaling pathways and molecules. According to our findings, upregulated TAB2 was correlated to stem cell-like properties of cervical cancer. Immunohistochemistry staining of TAB2 in normal and cervical cancer tissues was performed. The cell function experiments demonstrated that knockdown of TAB2 reduced the stemness of cervical cancer cells and, importantly, prevented cervical cancer progression. Collectively, the therapeutic scheme targeting TAB2 may provide an option for overcoming tumor relapse and chemoresistance of cervical cancer via obstructing stemness maintenance.